2020
DOI: 10.36590/kepo.v1i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Pemberian ASI Eksklusif dengan PASI terhadap Tumbuh Kembang pada Anak Usia 0-12 Bulan

Abstract: ASI sangat penting bagi pertumbuhan bayi. Pemberian ASI di Indonesia mengalami penurunan, masyarakat cenderung memilih PASI dbandingkan dengan ASI eksklusif dengan alasan bayi lebih cerdas. Penelitian ini bertujuan untuk mengetahui perbedaan antara pemberian ASI eksklusif dan PASI dengan tumbuh kembang anak usia 0-12 bulan. Penelitian ini menggunakan study komparatif dengan uji Mann Whitney Test. Tingkat perkembangan anak ditentukan dengan menggunakan lembar tes DDST. Teknik pengambilan sampel menggunakan tekn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…This is because breast milk contains taurine, a type of amino acid that functions as a neurotransmitter and plays a role in the maturation process of brain cells so that breast milk can be the best source for optimizing brain development, nervous tissue in the brain, and visual tissue. in infants (Ruhana et al, 2016); (Febrianti, 2018); (Lukman et al, 2020). A systematic review by Turner et al (2019) showed that 6 out of 13 studies described a positive relationship between breastfeeding and social-emotional development.…”
Section: Analysis Of Respondents' Characteristics Of Social-emotional...mentioning
confidence: 99%
“…This is because breast milk contains taurine, a type of amino acid that functions as a neurotransmitter and plays a role in the maturation process of brain cells so that breast milk can be the best source for optimizing brain development, nervous tissue in the brain, and visual tissue. in infants (Ruhana et al, 2016); (Febrianti, 2018); (Lukman et al, 2020). A systematic review by Turner et al (2019) showed that 6 out of 13 studies described a positive relationship between breastfeeding and social-emotional development.…”
Section: Analysis Of Respondents' Characteristics Of Social-emotional...mentioning
confidence: 99%
“…perkembangan bayi (Lukman et al, 2020) sedangkan yang disebut dengan ASI eksklusif adalah ASI yang diberikan kepada bayi sejak bayi dilahirkan selama 6 bulan, tanpa menambahkan dan atau mengganti dengan makanan atau minuman lain (kecuali obat, vitamin, mineral) (Kementrian Kesehatan Republik Indonesia), setelah 6 bulan bayi baru diberikan makanan atau minuman tetapi bayi 6 bulan keatas harus tetap diberikan ASI sampai berumur 2 tahun atau 2 tahun keatas (Riskesdas, 2014dan Departemen Kesehatan Republik Indonesia, 2014.…”
unclassified